Studi Tentang Pengaruh Latar Belakang Keluarga Terhadap Intensi Kewirausahaan Siswa SMKN Se-Kabupaten Bangka - Rizki Zulfickar; A. Sobandi (FKIP Unswagati, 2020)
AbstractThe problem in this study is the increase in unemployment in vocational high schools (SMK) caused by differences between student expertise and corporate culture. This study discusses the family background of influencing entrepreneurial intentions. The research method used was an explanatory survey using a questionnaire as an instrument using a Likert scale of 1-5. The population in this study were all students of class XII SMK in Bangka Regency. The sample in this study consisted of 320 students. Based on the results of the study showed that family background influences the intention of entrepreneurship significantly, both partially and simultaneously. Students who have an entrepreneurial family background have an average score higher than students who have a family background rather than an entrepreneur. The findings on the measurement of the intention of entrepreneurship plan indicators totaled to 4,51, meaning students have a high seriousness of thinking and planning regarding opening a new business. The second highest indicator is the desire of 4.12, meaning students have the desire to be independent and will be in the future. The highest indicator is a preference of 4,00, meaning that students prefer entrepreneurship as a career choice in the future when choosing a career again as a worker. It can be concluded that the intention of entrepreneurship students in vocational schools in Bangka Regency is high in category.Â Keywords: family background, entrepreneurship intention